2005
DOI: 10.1177/039463200501800406
|View full text |Cite
|
Sign up to set email alerts
|

Role of TLR4 Receptor Polymorphisms in Boutonneuse Fever

Abstract: The genetics of the interaction between host and microbes plays an essential role in the survival of the individual and attainment of longevity. The activation of toll-like receptor (TLR)4 plays a key role in natural and clonotypic immune responses. We evaluated whether TLR4 genotype is a component of genetic background protective versus rickettsiosis and whether this background influences longevity. We genotyped for +896A/G TLR4 polymorphism 78 patients affected by Boutonneuse fever, 78 age-matched controls a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 26 publications
0
14
1
Order By: Relevance
“…Interestingly, it has been demonstrated that the +869G single-nucleotide polymorphism of the TLR4 gene is overexpressed in BF patients with significant differences in the frequency of TLR genotypes and alleles between BF patients and age-matched controls. These data might be interpreted as one hypothetical basis for genetic susceptibility to BF [65]. …”
Section: Rickettsia Sppmentioning
confidence: 99%
“…Interestingly, it has been demonstrated that the +869G single-nucleotide polymorphism of the TLR4 gene is overexpressed in BF patients with significant differences in the frequency of TLR genotypes and alleles between BF patients and age-matched controls. These data might be interpreted as one hypothetical basis for genetic susceptibility to BF [65]. …”
Section: Rickettsia Sppmentioning
confidence: 99%
“…They have previously been genotyped for the following SNPs: +896A/G TLR4 SNP, À765G/C PTGS2 SNP (rs:20417) and À1708 G/A 5-Lo SNP (no available rs designation) ( Table 1). The procedures for detecting these SNPs have previously been described (Balistreri et al, 2005;Listì et al, 2008). Of 50 individuals, 40 were homozygous for wild-type alleles of +896A/ G TLR4 SNP, and 10 had one or two +896G alleles.…”
Section: Population Studied and Tlr4 Ptgs2 And 5-lo Genotypingmentioning
confidence: 99%
“…The DNA samples of the two control groups had been previously extracted from blood samples and genotyped for the six SNPs. The procedure for detecting the +896A/G and +1196C/T TLR4 and +2408 G/A and +2029C/T TLR2 SNPs ( Table 1) was based on Restriction Fragment Length Polymorphism-PCR (RFLP-PCR), restriction cleavage with Nco I, Hinf I, Mwo I and Mps I respectively (New England Biolabs, USA), and separation of DNA fragments by electrophoresis, as previously described [15,16]. The genotyping of -765G/C PTGS2 SNP was performed using RFLP-PCR and with Aci I (New England Biolabs, USA) restriction enzyme, as previously reported [17].…”
Section: Genotypingmentioning
confidence: 99%